2004
DOI: 10.1103/physreva.70.041201
|View full text |Cite
|
Sign up to set email alerts
|

Isomer-specific spectroscopy of metal clusters trapped in a matrix:Ag9

Abstract: Clusters of metal atoms at a fixed size can assume different structural arrangements, known as isomers, which may have nearly the same energy. Therefore, at given experimental conditions distribution of these isomers can be present. While the size selection is a relatively common technique, the isomer selection is not; it is therefore more difficult to obtain information about a single isomer. We report here on isomer-specific spectroscopy of Ag 9 clusters together with ab initio calculations allowing to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
66
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 25 publications
8
66
1
Order By: Relevance
“…R2PI measurements of Ag 8 in He droplets 38,40 have also been performed, they reveal a narrow structure centered at 3.96 eV and a shoulder at 3.99 eV corresponding clearly to the main absorption peak observed in neon and argon (FWHM equal to 56 meV, 0.1 eV, 0.2 eV in He, Ne, Ar). 7,41 Ag 9 In the case of Ag 9 in an argon matrix 42 the shape of the spectrum could only be explained by assuming that several isomers coexisted in the matrix. The absorption spectrum in neon is clearly different.…”
Section: A Comparison To Previous Experimental Resultsmentioning
confidence: 99%
“…R2PI measurements of Ag 8 in He droplets 38,40 have also been performed, they reveal a narrow structure centered at 3.96 eV and a shoulder at 3.99 eV corresponding clearly to the main absorption peak observed in neon and argon (FWHM equal to 56 meV, 0.1 eV, 0.2 eV in He, Ne, Ar). 7,41 Ag 9 In the case of Ag 9 in an argon matrix 42 the shape of the spectrum could only be explained by assuming that several isomers coexisted in the matrix. The absorption spectrum in neon is clearly different.…”
Section: A Comparison To Previous Experimental Resultsmentioning
confidence: 99%
“…But also in basic research the plasmon absorption and its modelling following Mie theory have proven a versatile tool in understanding cluster size effects, specific quantum mechanical influences [6] and interface effects [7]. Recently it was shown that also very small silver clusters of a few atoms only have intriguing properties and that their fluorescence is not only an ideal tool for fundamental researchers to determine their atomic and electronic structure [8,9] but that it might also be exploited in applications [10]. The aim of our research is to find means to produce samples of well defined metal clusters stabilized in protective matrices and to study their properties [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoclusters have interesting and promising properties in domains as diverse as optics, [1][2][3][4] catalysis, 5,6 and magnetism. [7][8][9][10] While some of these properties can arise for the cluster itself and can be studied in the gas phase, in most practical cases the nanoclusters are in interaction with their environment.…”
Section: Introductionmentioning
confidence: 99%